Effect of Dietary Carotenoids on Reproducers of Amazon River Prawn Macrobrachium amazonicum. Part 2: External Coloration, Accumulation of Astaxanthin in Body Tissues and Pigment Stability in Feed - Costa, Daniel Pereira da; Castilho, Claudiana de Lima; Santos, Uclédia Roberta Alberto dos; Gemaque, Tainára Cunha; Damasceno, Leandro Fernandes; Lima, Jô de Farias; Filho, Kleber Campos Miranda (Journal of Agricultural Studies, 2021)
The color is an important factor to distinguish the commercialized Amazon river prawns. The accumulation of pigments in the body can vary according to the prawn’s diet. In this work, ethanolic extracts of “buriti” and annatto rich in pigments were obtained and tested comparatively with synthetic astaxanthin in the feeding of adults of Macrobrachium amazonicum, together with a control group without pigments and a newly captured wild group. Levels of body pigments were measured using UV reflective spectroscopy and external staining by colorimetry. Differences were observed in the accumulation of astaxanthin in body tissues, differences in saturation between genders and that annatto extract has greater stability in the feed after water immersion (P˂0.05). Further studies are recommended to verify the ideal dosage of natural pigments in relation to synthetic astaxanthin that benefits the productive development of prawns.